Epidemiology and outcomes of patients with penetrating trauma in Incheon Metropolitan City, Korea based on National Emergency Department Information System data: a retrsopective cohort study - Youngmin Kim; Byungchul Yu; Se-Beom Jeon; Seung Hwan Lee; Jayun Cho; Jihun Gwak; Youngeun Park; Kang Kook Choi; Min A Lee; Gil Jae Lee; Jungnam Lee (Journal of Trauma and Injury)
Purpose Patients with penetrating injuries are at a high risk of mortality, and many of them require emergency surgery. Proper triage and transfer of the patient to the emergency department (ED), where immediate definitive treatment is available, is key to improving survival. This study aimed to evaluate the epidemiology and outcomes of patients with penetrating torso injuries in Incheon Metropolitan City. Methods Data from trauma patients between 2014 and 2018 (5 years) were extracted from the National Emergency Department Information System. In this study, patients with penetrating injuries to the torso (chest and abdomen) were selected, while those with superficial injuries were excluded. Results Of 66,285 patients with penetrating trauma, 752 with injuries to the torso were enrolled in this study. In the study population, 345 patients (45.9%) were admitted to the ward or intensive care unit (ICU), 20 (2.7%) were transferred to other hospitals, and 10 (1.3%) died in the ED. Among the admitted patients, 173 (50.1%) underwent nonoperative management and 172 (49.9%) underwent operative management. There were no deaths in the nonoperative management group, but 10 patients (5.8%) died after operative management. The transferred patients showed a significantly longer time from injury to ED arrival, percentage of ICU admissions, and mortality. There were also significant differences in the percentage of operative management, ICU admissions, ED stay time, and mortality between hospitals. Conclusions Proper triage guidelines need to be implemented so that patients with torso penetrating trauma in Incheon can be transferred directly to the regional trauma center for definitive treatment.